EVALUATION OF PHYTOCONSTITUENTS, ANTIBACTERIAL, ANTIOXIDANT AND CYTOTOXIC ACTIVITY OF VITEX NEGUNDO L. AND TABERNAEMONTANA DIVARICATA L. - REBECCA THOMBRE,; RAJSHREE JAGTAP,; NEETA PATIL, (International Journal of Pharma and Bio Sciences, 2013)
The aim of present study was to evaluate antioxidant and antibacterial activity of Vitex negundo L.and Tabernaemontana divaricata L.Methanolic extract of V. negundo L. was found to contain142.96 ± 6.73 mg GAE/gm dry weight of phenolics and167.88 ± 4.80 mg QE /gm dry weightflavonoids. The leaf extracts of V. negundo L.demonstrated higher antioxidant activity as compared to T. divaricataL. Both the plant extracts showed broad spectrum antibacterial activity. The cytotoxic activity of theextracts of V. negundo L.and T. divaricata L. were assessed on THP-1 leukemia cell line using MTT assay and both the plants demonstrated cancer cell inhibitory activity.Both these shrubs have potential applications in pharmaceutical industry and medicine due to their phytoconstituents, antioxidants, antibacterial and anticancer activities.